Excavation Safety Modeling Approach Using BIM and VPL - Lee, Do Yeop; Skibniewski, Miroslaw; Ali, Ahmad K.; Khan, Numan; Park, Chansik (Advances in Civil Engineering, 2019)
Soil excavation is a fundamental step of building and infrastructure development. Despite strong enforcement of construction best practices and regulations, accidents in construction industry are comparatively higher than other industries. Likewise, significant increase in injuries and fatalities are recently reported on geotechnical activities such as excavation pits and trenches. Academic researchers and industry professionals have currently devoted vital attention to acquire construction safety in preconstruction phase of the project. They have developed various algorithms to enhance safety in preconstruction phase such as automated generation of scaffolding and its potential risk analysis, checking BIM model for fall risks, and limited access zone allocation in wall masonry. However, safety in geotechnical works at preconstruction phase is yet unexplored. This paper proposed automatic safety rule compliance approach for excavation works leveraging algorithmic modeling tools and BIM technologies. The focused approach comprises of the following three modules: information extraction and logic design (IELD), information conversion and process integration (ICPI), and automodeling and safety plan generation (ASPG). Specifically, the scope of the paper is limited to major risks such as cave-ins, fall, safety egress, and prohibited zones risks. A set of rules-based algorithms was developed in commercially available software using visual programming language (VPL) that automatically generates geometric conditions in BIM and visualizes the potential risks and safety resources installation along with their quantity take-off and optimized locations. A case study has been presented to validate the proof of concept; automated modeling tool for excavation safety planning generated the required results successfully. It is anticipated that the proposed approach has potential to help the designers through automated modeling and assist decision makers in developing productive and practical safety plans compared to the conventional 2D plans for excavation works at the preconstruction phase. Moreover, it is realized that the same approach can be extended to other rule-dependent subjects in construction.